Profil Hematologi Induk Domba dengan Pemberian Pakan Flushing Berbeda: Hematologic Profile of The Ewes by Giving Different Flushing Feed - Dewi Apri Astuti; NE Maharani; D Diapari; L Khotijah; K Komalasari (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2022)
This study aimed to analyze the hematological profiles of late pragnant sheep fed by flushing ration. This research used twelve multiparous lactating ewes of thin tale local sheep, with the average body weight of 29,75 ± 6,20 kg head-1 and placed in individual sheep pen. This research used a randomized block design (RBD) with 4x3 that was grouped based on body weight of ewes. The treatments consisted of R1 = treatment without flushing, R2 = flushing treatments before and after matting, R3 = flushing treatment same with R2 plus during in the middle of pregnancy, R4 = flushing treatment same with R3 plus during at the end of pregnancy. Ratio forages and concentrate in the ration were 30:70% based on dry matter basis. The observed variables were hematological profiles and nutrient intake. The data were analyzed using ANOVA and the significance of treatments was continued to have the analysis through Duncan test. The results showed that the treatments did not affect significantly to the hematological profiles nor the nutrients intake, except to the amount of white blood cell. The conclusion of this research was the different flushing management for the late pregnancy ewes did not give a significant effect on hematological profiles and nutrient consumption. Key words: flushing, hematology, local thin tale sheep ewes, mating